Evolution of Indian Influenza A (H1N1) Hemagglutinin Strains: A Comparative Analysis of the Pandemic Californian HA Strain - Pushan, Shilpa Sri; Samantaray, Mahesh; Rajagopalan, Muthukumaran; Ramaswamy, Amutha (Frontiers in Molecular Biosciences, 2023)
The need for vaccine/inhibitor design becomes inevitable concerning the emerging epidemic and pandemic viral infections, and the recent outbreak of the Influenza A (H1N1) virus is one such example. From 2009–2018, India faced severe fatalities due to the outbreak of the Influenza A (H1N1) virus. In this study, the potential features of reported Indian H1N1 strains are analyzed in comparison with their evolutionarily closest pandemic strain, A/California/04/2009. The focus is laid on one of its surface proteins, Hemagglutinin (HA), which imparts a significant role in attacking the host cell surface and its entry. The extensive analysis made, in comparison with the A/California/04/2009 strain, revealed significant point mutations in all Indian strains reported from 2009 to 2018. Due to these mutations, all Indian strains disclosed altered features at the sequence and structural levels, which are further presumed to be associated with their functional diversity as well. The mutations observed with 2018 HA sequence such as S91R, S181T, S200P, I312V, K319T, I419M, and E523D might improve the fitness of the virus in a new host and environment. The higher fitness and decreased sequence similarity of mutated strains may compromise therapeutic efficacy. In particular, the mutations, observed commonly, such as Serine-to-Threonine, Alanine-to-Threonine, and Lysine-to-Glutamine at various regions alter the physico-chemical features of receptor binding domains, N-glycosylation and epitope binding sites, etc. when compared with the reference strain. Such mutations render diversity among all Indian strains, and the structural and functional characterization of these strains becomes inevitable. In this study, we observed that mutational drift results in the alteration of the receptor binding domain, the generation of new variant N-glycosylation along with novel epitope binding sites, and modifications at the structural level. Eventually, the pressing need to develop potentially distinct next-generation therapeutic inhibitors against the HA strains of Indian Influenza A (H1N1) virus is also highlighted here.